Evolution of the modulated electron beam in supercritical plasma: simulation of initial-boundary problem - Anisimov, I.O.; Kiyanchuk, M.J. (Вопросы атомной науки и техники, 2006)
Evolution of the modulated electron beam moving through the supercritical plasma was studied in this work via computer simulation using PIC method. Results obtained correspond qualitatively to the experimental data. It was shown that concurrence between the resonant mode growing from the noise level and the non-resonant signal mode leads to the suppression of the non-resonant mode In contrast to previous calculations it is shown that the resonance instability occurs in the broad frequency band. Dependence of the peak amplitude of the signal on its’ initial value was obtained. Frequency band expansion (for the resonant instability) can be explained by processes of l-s decay of initial Langmuir wave.